Estudo de fibras do bagaço de caju (Anacardium occidentale L.) no metabolismo normal e na obesidade em camundongos - Carvalho, Diana Valesca (2018)
The dietary fibers intake plays an important role in the prevention of obesity and associated metabolic disorders. This work aims to evaluate the influence of cashew bagasse fibers on normal metabolism and high fat diet-induced obesity in mice. Cashew bagasse was obtained after the extraction of cashew juice submitted to washing treatment, then frozen, lyophilized and ground, obtaining the integral cashew fiber (FcI). Part of this fiber was subjected to the extraction with hexane and methanol, resulting in cashew fiber without low molecular weight metabolites (FcSM). In the normal metabolism, the two fibers obtained were used in the ration of normal mice in the proportion of 10% for 15 weeks. After treatment, blood glucose, total cholesterol and fractions, triglycerides, urea, liver enzymes aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were analyzed. Histological analyses of the liver, Malondialdehyde (MDA) and non-protein sulfhydryl groups (NP-SH), as well as hormonal dosages of insulin, leptin and ghrelin were also performed. Mice from the FcSM group significantly increased water intake, reduced glycemia, insulinemia, ALT and plasma ghrelin concentration. FcI promoted abdominal adiposity, hyperlipidemia (total cholesterol, LDL and triglycerides), hyperleptinemia, in addition to increasing plasma concentrations of AST. In obesity, only FcSM was evaluated for having positive effects on normal metabolism. The mice were submitted to a normal diet (ND), a high fat diet (HFD) or a high fat diet supplemented with 10% FcSM (HFD-FcSM). After 15 weeks, measures of body weight, abdominal fat, serum glucose, lipid profile, insulin, leptin and ghrelin satiety hormones, amylase and lipase digestive enzymes, AST and ALT, hepatic tissue analysis, inflammatory mediators TNF-α, IL-6 and adiponectin. In addition, metabolomic analysis was performed based on nuclear magnetic resonance (NMR) in the serum and feces of the animals. It was verified that FcSM exerted preventive antiobesity effect, reducing body weight, abdominal fat, glycemia, insulinemia, serum triglycerides and hepatic steatosis. Fiber modulated the secretion of satiety hormones, the secretion of digestive enzymes and the cytokines involved in the inflammatory process. In addition, NMR showed a probable prebiotic effect of FcSM with production of propionic and butyric acids in feces and acetic acid in the serum of animals. It is concluded that in normal metabolism, FcI increased abdominal fat and altered the lipid metabolism of mice, whereas FcSM can be used as a functional ingredient for the preparation of food products as an integral part of a healthy eating. In obesity, FcSM prevented the obese state through hormonal modulation, enzymatic and inflammatory response, as well as the production of short chain fatty acids (SFCA).